Beef improvement - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
One hundred beef-type cattle sixty heifers and forty bulls from Guatemala and another sixteen bulls and forty heifers from Mexico have been imported by Belize to improve the growth rate and meat quality of Belizian cattle. After the required...